Cofilin 2 in Serum as a Novel Biomarker for Alzheimer’s Disease in Han Chinese - Sun, Yingni; Liang, Lisheng; Dong, Meili; Li, Cong; Liu, Zhenzhen; Gao, Hongwei (Frontiers in Aging Neuroscience, 2019)
The identification of biomarkers of Alzheimer's disease (AD) is an important and urgent area of study, not only to aid in the early diagnosis of AD, but also to evaluate potentially new anti-AD drugs. The aim of this study was to explore cofilin 2 in serum as a novel biomarker for AD. The upregulation was observed in AD patients and different AD animal models compared to the controls, as well as in AD cell models. Memantine and donepezil can attenuate the upregulation of cofilin 2 expression in APP/PS1 mice. The serum levels of cofilin 2 in AD or mild cognitive impairment (MCI) patients were significantly higher compared to controls (AD: 167.9±35.3 pg/mL; MCI: 115.9±15.4 pg/mL; Control: 90.5±27.1 pg/mL; p<0.01). A significant correlation between cofilin 2 levels and cognitive decline was observed (r=–0.792; p<0.001). The receiver operating characteristic curve (ROC) analysis showed the area under the curve (AUC) of cofilin 2 was 0.957, and the diagnostic accuracy was 80%, with 93% sensitivity and 87% specificity. The optimal cut-off value was 130.4 pg/ml. Our results indicate the possibility of serum cofilin 2 as a novel and non-invasive biomarker for AD. In addition, the expression of cofilin 2 was found to be significantly increased in AD compared to vascular dementia (VaD), and only an increased trend but not significant was detected in VaD compared to the controls. ROC analysis between AD and VaD showed that the AUC was 0.824, which could indicate a role of cofilin 2 as a biomarker in the differential diagnosis between AD and VaD.